Technology Map: A Text Mining and Network Analysis Approach - Arif Rakhman Hakim; Taufik Djatna; Ade Febransyah (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Information of technology development is indispensable for research planning. This information is needed by researcher to determine research topics which he will contribute. For journal editor, this information is needed to evaluate research paper draft. Unfortunately, technology development is unable to be measured directly. To measure the development, several methods have been developed using patent and journal as its data. In this work we focused on development of technology map and its measurement in a method to provide information of technology development from Indonesian research journals using text mining and network analysis. The map helps stakeholders to plan their researches. Using journal data from agro-industrial technology, the method is able to identify relation between researches, thus we can develop the time line of the research area. The method can also cluster the researches into nineteen research areas and measure its popularity, importance, affinity to particular group, research type whether breakthrough or incremental, research group retention time, and its saturation.